L’Orientation d’Aide Mutuelle Dans le Counseling Pour Adultes - Peavy, R. Vance; Linteau, Marie-Andrée (Canadian Journal of Counselling and Psychotherapy, 2012)
Adults Helping Adults (AHA), as a form of cooperative counselling for adults, has been preceded by Harvey Jackins' Re-evaluation Counselling, John Southgate's Karen Homey Counselling, and John Heron's Reciprocal Counselling. All of these counselling approaches have one thing in common: the principle of help-giver/ help-seeker role exchange. AHA is an approach to adult counselling which is organized around the mutual aid orientation. The concept of orientation is very important. If we have a helpless orientation, then we are on a deteriorating path in life. On the other hand, if we have a helpful orientation, then we are on a reward-finding path which helps us become more able rather than less. The mutual aid orientation has five elements: the existential (focus is on the concrete problems people actually have); transformation (coping and learning to benefit from change); reciprocity ("I'll help you and you help me."); helper principle (how can the help-seeker get the benefits of the helping process usually experienced only by the help-giver?); democratic ideal (every person, including the help-seeking, should have a right to say yes and no to what happens to them); creativity (getting free from frozen patterns). AHA is a series of regular, reciprocal exchanges between two persons which helps both to (a) gain emotional mastery; (b) get and give useful guidance about expectable problem and possible responses to them; and (c) provide self- and performance-validating feedback.